Comparison of Postural Stability and Balance Between Musicians and Non-musicians - Nusseck, Manfred; Spahn, Claudia (Frontiers in Psychology, 2020)
Good postural stability and balance provide a basis for optimal movement. For instrumental musicians, particular postures are demanded during long periods of playing and practising. These postures can potentially also affect the postural control system even in situations when the musician is not playing the instrument. The goal of this exploratory study was to measure the postural stability and balance of instrument musicians in non-instrumental situations. By comparing these measures with a control group of non-musicians, postural differences were identified which can be ascribed to certain playing positions arising from playing the instrument. The measurement technique used was a pressure platform (Zebris force plate) to record static posturography. The postural sway of the centre of pressure (COP) and the postural balance (body weight distribution) in a standing position were measured in 390 students including music students (n=346) and a control group (n=44). The analyses revealed significant differences for specific instrumental groups. 23% of the pianists, 25% of the upper strings players and 33% of the guitar players showed a weight distribution significantly shifted more to the left compared to the control group (9%). In contrast, 23% of the lower strings players and 33% of the percussionists were found to stand more to the right side than the control group (5%). The results indicate that there are certain unbalanced postural patterns in musicians, outside of the music performance situation, which can be provoked by instrumental playing postures. As postural misalignments can lead to severe postural disorders in older age, preventive activities to improve postural stability and balance should be considered in instrumental education, not only during, but also outside of instrumental playing situations.